Changing Demographics in Laparoscopic Cholecystectomy Performed in the United States: Hospitalizations from 1998 to 2010. Issue 7 (July 2014) - Tucker, James J.; Grim, Rod; Bell, Ted; Martin, Jennifer; Ahuja, Vanita
In the clinical experience at a community hospital, younger patients appear to be receiving more laparoscopic cholecystectomy (LC). The purpose of this study was to determine if LC is increasing in the younger patient population and if obesity is associated with the increase in LC. Patients undergoing LC were identified from the Healthcare Cost Utilization Project Nationwide Inpatient Sample database. There were 4, 449, 643 LCs from 1998 to 2010. Patients 15 to 24 years of age had the largest increase in LC (3.2%) and obesity (10.8%) from 1998 to 2010. In the 15- to 24-year age group, the following variables were associated with obesity: female, white, private payer, nonteaching hospital, urban location, southern region, large hospital bed size, and 31 Charlson group, all P < 0.05. Additionally in the 15- to 24-year age group, median length of stay (nonobese 2 days vs obese 3 days) and median cost (nonobese $19, 170 vs obese $22, 802) were both increased ( P < 0.001). The percentage of younger people having LC is increasing with highest increases in the obese population. The obese youth also have longer length of stay with an increase in hospital cost. These results suggest a rising disease burden associated with obesity among people ages 15 to 24 years. Gallstone disease burden will likely increase with the increase in prevalence of obesity and would add to healthcare economic burden.